1982
DOI: 10.1037/0003-066x.37.11.1159
|View full text |Cite
|
Sign up to set email alerts
|

The employment of 1979 and 1980 doctorate recipients in psychology.

Abstract: In 1975, the American Psychological Association initiated the Doctorate Employment Survey to assess the employment status of recent doctorate recipients in psychology. This report summarizes the results of the 1979 and 1980 surveys. As was found in the 1975-1978 surveys, the unemployment rate for these individuals is low (1.7%), and the vast majority of those employed in full-time positions have jobs that are related to psychology (95.2%). The academic job market, especially in universities, continues to decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 16 publications
(16 reference statements)
0
38
0
Order By: Relevance
“…Approximately 22% of our sample identified themselves primarily as private practitioners. This percentage was con- (Stapp & Fulcher, 1982;Stapp, Fulcher, & Wicherski, 1984). Of those respondents whose primary affiliation was not private practice (n = 521, 78.5%), 298 (57.1%) indicated that they engaged in some part-time private practice.…”
Section: Primary Institutional Affiliationsmentioning
confidence: 99%
“…Approximately 22% of our sample identified themselves primarily as private practitioners. This percentage was con- (Stapp & Fulcher, 1982;Stapp, Fulcher, & Wicherski, 1984). Of those respondents whose primary affiliation was not private practice (n = 521, 78.5%), 298 (57.1%) indicated that they engaged in some part-time private practice.…”
Section: Primary Institutional Affiliationsmentioning
confidence: 99%
“…Demand h~s kept pace with the increases in the doctorally trained population; unemployment rates for all psychologists and for new doctorate recipients have hovered around 2% for the past decade (Stapp & Fulcher, 1982;Stapp, Fulcher, & Wicherski, 1984). Demand h~s kept pace with the increases in the doctorally trained population; unemployment rates for all psychologists and for new doctorate recipients have hovered around 2% for the past decade (Stapp & Fulcher, 1982;Stapp, Fulcher, & Wicherski, 1984).…”
Section: Changing Patterns Of Employment For Doctoral-level Psychologmentioning
confidence: 99%
“…Data are from the following sources: [Employment settings of 1983 doctorates in psychology] by G. Pion, 1985a, unpublished analyses;"The Employment of 1979 and1980 Doctorate Recipients in Psychology" by J. Stapp and R. Fulcher, 1982, American Psychologist, 37, pp. 1159-1185and "The Employment of Recent Doctorate Recipients in Psychology: 1975Through 1978" by J. Stapp, R. Fulcher, S. D. Nelson, M. S. Pallak, and M. Wicherskl, 1981.…”
Section: Changing Patterns Of Employment For Doctoral-level Psychologmentioning
confidence: 99%
“…For the most part, current counseling and clinical psychology graduate students are trained to be practitioners. For example, only 14% of 1980 counseling psychology graduates were employed in university positions one year after receiving their degree versus 34% of 1975 graduates (Stapp & Fulcher, 1982); only 2% of current doctoral clinical students aspire to academic research careers (Marwit, 1983); research activity while a counseling graduate student may hurt a person's rating on intern and employment suitability (Hirsch & Stone, 1983). Therefore, one must ask: How valuable to most potential students are these studies that only consider the research and professional leadership dimension of graduate programs?…”
Section: Usefulness Of These Studiesmentioning
confidence: 99%